Ensino a distância via internet: uma opção para melhoria de qualidade do ensino superior - Morais, Aírton Pedroso de (2006)
Nowadays, virtual learning has been considered as one of the most important alternatives to conventional teaching. It has already started to appear as a new teaching option due to its significant advantages, widespread operating area and flexibility, filling in the gaps left by the conventional teaching-learning system mainly for those people who have to study and work simultaneously. Despite its increasing importance, the virtual learning process has been challenged to come up with results that are similar and even better than the results gained through conventional educational methods. Some major concerns such as quality of teaching, growing demand for further studies and continuous developments in Information Technology have placed the issue of virtual learning in the centre of public attention. The present work is a qualitative research whose main aim is to study the viability, implementing conditions, changes and impact on the teaching-learning process caused by virtual learning through the Internet in the Cenecistas Colleges that are located in the state of Rio Grande do Sul, Brazil. This work also presents the theoretical support based upon scientific approaches to virtual learning, its main features, its historical evolution and the process of Virtual Learning in Brazil. In addition, the emerging educational paradigms, the virtual learning lawful aspects in Brazil as well as some other relevant concepts such as Internet, quality, quality of service and productivity are also presented. The methodological approach, arrangement of research, study group, data collecting technique and the theoretical approaches are presented in the Methods and Technique chapter. The results and discussions were done through analysis and were demonstrated in graphics and the contribution of the Quality Function Development (QFD) was used as a method to establish the relationship among quality features and requirements with special attention to the quality comparative table containing the results based upon scientific evidence that are aligned with the aims of the present study. This work also features the basic guidelines for the implementation of virtual learning programmes through on-line teaching-learning tools. Some application tools are also suggested for the designing of educational virtual environments: blackboard-learning system, micro power learning suite, teleduc, gestum, webct and aulanet. The application tools are described with their respective methodologies, management criteria, development of contents, evaluation and promotion of virtual communities. The conclusion suggests possible implementation of relevant virtual learning initiatives as well as some ways in which institutions can become more competitive.